Calmodulin antagonist enhances DR5‐mediated apoptotic signaling in TRA‐8 resistant triple negative breast cancer cells. Issue 7 (16th April 2018) - Fancy, Romone M.; Kim, Harrison; Napier, Tiara; Buchsbaum, Donald J.; Zinn, Kurt R.; Song, Yuhua
Abstract: Patients with triple negative breast cancer (TNBC) have no successful "targeted" treatment modality, which represents a priority for novel therapy strategies. Upregulated death receptor 5 (DR5) expression levels in breast cancer cells compared to normal cells enable TRA‐8, a DR5 specific agonistic antibody, to specifically target malignant cells for apoptosis without inducing normal hepatocyte apoptosis. Drug resistance is a common obstacle in TRAIL‐based therapy for TNBC. Calmodulin (CaM) is overexpressed in breast cancer. In this study, we characterized the novel function of CaM antagonist in enhancing TRA‐8 induced cytotoxicity in TRA‐8 resistant TNBC cells and its underlying molecular mechanisms. Results demonstrated that CaM antagonist(s) enhanced TRA‐8 induced cytotoxicity in a concentration and time‐dependent manner for TRA‐8 resistant TNBC cells. CaM directly bound to DR5 in a Ca 2+ dependent manner, and CaM siRNA promoted DR5 recruitment of FADD and caspase‐8 for DISC formation and TRA‐8 activated caspase cleavage for apoptosis in TRA‐8 resistant TNBC cells. CaM antagonist, trifluoperazine, enhanced TRA‐8 activated DR5 oligomerization, DR5‐mediated DISC formation, and TRA‐8 activated caspase cleavage for apoptosis, and decreased anti‐apoptotic pERK, pAKT, XIAP, and cIAP‐1 expression in TRA‐8 resistant TNBC cells. These results suggest that CaM could be a key regulator to mediate DR5‐mediated apoptotic signaling, and suggests a potential strategy for using CaM antagonists to overcome drug resistance of TRAIL‐based therapy for TRA‐8 resistant TNBC. Abstract : In this study, we characterized the novel function of Calmodulin (CaM) antagonist in enhancing TRA‐8‐induced cytotoxicity in TRA‐8‐resistant triple negative breast cancer (TNBC) cells and its underlying molecular mechanisms. Results demonstrated that CaM antagonist(s) enhanced TRA‐8‐induced cytotoxicity in a concentration‐ and time‐dependent manner for TRA‐8‐resistant TNBC cells. CaM directly bound to death receptor 5 (DR5) in a Ca 2+ ‐dependent manner, and CaM siRNA promoted DR5 recruitment of FADD and caspase‐8 for death‐inducing signaling complex (DISC) formation and TRA‐8‐activated caspase cleavage for apoptosis in TRA‐8‐resistant TNBC cells. CaM antagonist, trifluoperazine, enhanced TRA‐8 activated DR5 oligomerization, DR5‐mediated DISC formation, and TRA‐8‐activated caspase cleavage for apoptosis, and decreased anti‐apoptotic pERK, pAKT, XIAP, and cIAP‐1 expression in TRA‐8‐resistant TNBC cells.